RELIGIUSITAS SEBAGAI PREDIKTOR KEPERCAYAAN DIRI AKADEMIK DALAM PENYELESAIAN TUGAS AKHIR MAHASISWA UIN PALANGKA RAYA - Ningsih, Nony Wahyu; Masitoh, Dwi; Ramadhani, Hidayati; Surawan (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2026)
The pressure from completing a final project can make students lose confidence in doing research. Religiosity is seen as one of the factors that can boost students' academic self-confidence. This study aims to see how students' academic self-confidence in completing their final projects at UIN Palangka Raya is influenced by their level of interest in religion. This study uses a quantitative approach with an explanatory research design. The research sample consists of 61 final-year students who are writing their thesis, and they were selected using the purposive sampling technique. Data was collected using a questionnaire with a Likert scale that has been tested for validity and reliability. The data analysis was carried out using the simple linear regression method, and the IBM SPSS Statistics software was used to make the process easier. The study shows that religiosity has a significant effect on students' academic self-confidence. The significance value is 0.000 (p < 0.05), and the coefficient of determination (R²) is 0.632. This finding shows that students' academic self-confidence increases because of their religious beliefs. This study shows that increasing religious values in higher education settings can help students be more mentally prepared for the demands of their academic work.